Strategic Geographic Targeting in Community Development: Examining the Congruence of Political, Institutional, and Technical Factors. - Thomson, Dale E. (Urban Affairs Review, 2011)
Strategic geographic targeting (SGT) of community development resources has become increasingly common among cities attempting to enhance the impact of limited community development resources. Through an examination of a unique geographically targeted community development initiative undertaken by the City of Detroit, the author shows that despite environmental changes that made adoption of SGT politically viable, efforts to implement SGT, particularly efficiency-based SGT (EB-SGT), were hampered by political, institutional, and technical factors. The author discusses the likely impact that these factors have on the potential for adopting and successfully implementing EB-SGT as a community development strategy in other cities. Reprinted by permission of the publisher.